A HPLC Method for the Quantitative Determination of N-(2-hydroxy-5-nitrophenylcarbamothioyl)-3,5-imethylbenzamide in Biological Samples - Skidan, Igor (2011)
A sensitive and simple HPLC method was developed for the determination of a novel compound, a potential anti-cancer drug, N-(2-hydroxy-5-nitrophenylcarbamothioyl)-3,5-dimethylbenzamide (DM-PIT-1), a member of the new structural class of non-phosphoinositide small molecule antagonist of phosphatidylinositol-3,4,5-trisphosphate–pleckstrin-homology domain interactions, in mouse plasma and tumor tissue homogenates. The chromatographic separation of DM-PIT-1 was achieved on C18 column using isocratic elution with acetonitrile-water (70:30) containing 0.1% formic acid (v/v). DM-PIT-1 was detected by UV absorbance at 320 nm and confirmed by LC-MS. The extraction of the DM-PIT-1 from the plasma and tumor tissue with methylene chloride resulted in its high recovery (70–80%). HPLC calibration curves for DM-PIT-1 based on the extracts from the mouse plasma and tumor tissue samples were linear over a broad concentration range of 0.25–20 μg/ml/g, with intra/inter-day accuracy of 95% and the precision of variation below 10%. The limits of detection and quantification were 0.1 ng and 0.2 ng respectively. The described method was successfully applied to study the pharmacokinetics of the DM-PIT-1 following the parenteral injections of DM-PIT-1 entrapped in 1,2-Disteratoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene-glycol)-2000] (PEG-PE) micelles.